2014
DOI: 10.1603/me13107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Mass Trapping With BG-Sentinel Traps for Dengue Vector Control: A Cluster Randomized Controlled Trial in Manaus, Brazil

Abstract: The objective of this study was to assess the effectiveness of BG-Sentinel (BGS) traps for mass trapping at the household level to control the dengue vector, Aedes aegypti (L.), in Manaus (Brazil) by performing a cluster randomized controlled trial. After an initial questionnaire and baseline monitoring, 6 out of 12 clusters were randomly allocated to the intervention arm, where participating premises received one BGS trap for mass trapping. The other six clusters did not receive traps and were considered as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 33 publications
0
95
1
2
Order By: Relevance
“…aegypti , their ability to suppress Aedes population is variable. In Brazil [47] no reduction in the Aedes population was detected in the treated areas while in Puerto Rico they managed to suppress the Ae. aegypti population [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti , their ability to suppress Aedes population is variable. In Brazil [47] no reduction in the Aedes population was detected in the treated areas while in Puerto Rico they managed to suppress the Ae. aegypti population [48].…”
Section: Discussionmentioning
confidence: 99%
“…These traps come in different designs and some contain insecticides or incorporate pyriproxyfen to kill the progeny [45, 46]. In a randomised control trial using BG sentinel trap, trapping slightly reduced the density of Aedes in the experimental area compared to the control area [47]. However, in a trial using CDC autocidal gravid trap (AGO) there was a significant reduction in adult Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Andreas Rose (Biogents AG, Germany) discussed the relevance of deploying combination of source reduction and traps for host-seeking females (BGS), or traps for gravid females (CDC-AGO & BG-GAT) to sustain vector control. Originally used in surveillance and monitoring, research has demonstrated the potential of BGS traps as a vector control tool [58]. Studies with area-wide use of AGO in Puerto Rico have shown an 80% reduction in the density of female Ae.…”
Section: Session 4: Private-public Partnership For the Development Ofmentioning
confidence: 99%
“…O dengue caracteriza-se como uma arbovirose de rápida propagação em áreas tropicais e subtropicais (DEGENER et al, 2014). A transmissão ocorre aos seres humanos através da picada de mosquitos Aedes aegypti.…”
Section: Etiologia Do Dengueunclassified